ILC Vanguard Initiative - Takahashi Tohru (EPJ Web of Conferences)
The ILC Vanguard Initiative was established August 2023 with the premise of siting the ILC in Japan. This includes the construction of a new social model, the creation of new values, and the implementation of the plan. The primary focus is to prepare for urban development and future growth at the prospective site locations, which require extensive surveys, facility reviews, and careful planning. In this talk we report motivation and recent activities of the ILC Vanguard Initiative.